2021
DOI: 10.1093/ijnp/pyab067
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Role of Dopamine in the PFC and NAc During Exposure to Cocaine-Associated Cues

Abstract: Background Dopamine neurotransmission plays a critical role in reward in drug abuse and drug addiction. However, the role of dopamine in the recognition of drug-associated environmental stimuli, retrieval of drug-associated memory and drug-seeking behaviors is not fully understood. Methods Roles of dopamine neurotransmission in the prefrontal cortex (PFC) and nucleus accumbens (NAc) in the cocaine conditioned place preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The reduction was greater than previously reported with flupirtine 26 , a less selective structural precursor of retigabine that activates Kv7.2/7.3 and other channels 27 . The behavioral reduction with retigabine may reflect decreased dopamine transmission, as similar doses of retigabine reportedly decreased the enhancement of striatal and cortical dopamine levels associated with noncontingent administration of cocaine 16 , which appear necessary for the acquisition of CPP 28 .…”
Section: Retigabine Reduces Cocaine Cppmentioning
confidence: 95%
“…The reduction was greater than previously reported with flupirtine 26 , a less selective structural precursor of retigabine that activates Kv7.2/7.3 and other channels 27 . The behavioral reduction with retigabine may reflect decreased dopamine transmission, as similar doses of retigabine reportedly decreased the enhancement of striatal and cortical dopamine levels associated with noncontingent administration of cocaine 16 , which appear necessary for the acquisition of CPP 28 .…”
Section: Retigabine Reduces Cocaine Cppmentioning
confidence: 95%
“…Typically, frontal cortex neurons propagate reward-related signals via D1DR. [59][60][61][62] Though cellular level astrocytes response to dopamine via each receptor is well investigated, it is not much investigated that the detail mechanism of astrocytes to dopamine in frontal cortex under physiological condition. [63][64][65][66] To delineate the contributions of D1DR and D2DR to the activation of neurons and astrocytes under IG glucose injection, the effect of D1DR and D2DR antagonist on CaMKII-GCamp7f and Mlc-YC signals were assessed using fiber photometry (Fig.…”
Section: Neuropod Cells Facilitate the Immediate Activation Of The Fr...mentioning
confidence: 99%
“…Cocaine has been demonstrated to possess an elevated abuse potential, with experimental studies reporting it induces place preference conditioning and readily acts as reinforcer for drug self-administration [131][132][133][134]. Di Chiara and Imperato tested the effect of cocaine on extracellular dopamine content in two terminal dopaminergic brain areas of rats (the dorsal caudate nucleus and the nucleus accumbens septi), and found that the drug has the capacity to increase dopamine concentrations in both the areas, but especially in the nucleus accumbens, postulating that this ability could be a key element of drugs of abuse [135].…”
Section: Abuse Potential Dependence and Tolerancementioning
confidence: 99%